FOREIGN LANGUAGE EDUCATIONAL ENVIRONMENT OF A MODERN UNIVERSITY IN UKRAINE - Yuliia Rudnik; Lada Petryk; Natalia Kosharna (Borys Grinchenko Kyiv Metropolitan University, 2024)
Most universities strive to create a favourable educational environment according to modern trends and requirements. The paper analyzes and systematizes the essence of the concepts «educational environment» and «foreign-language environment» based on the research of Ukrainian and foreign scholars. Drawing on the typology of educational environments, the authors of the paper refine the understanding of the concept of a «foreign-language educational environment» based on the literature reviews. Considering the challenges of the present, caused by COVID-19, the post-COVID era, and the war in Ukraine, the factors influencing the transformation of the modern educational environment are presented and discussed. The paper organizes existing research on the explored problem and presents the authors' vision of the contemporary educational environment of a university under modern conditions. It includes the description of technologies used to address various educational needs and to meet the technological requirements. Therefore, the typical features of such an educational environment are personalization, flexibility, engagement, interactivity, availability, and multisensory and multimode experience. The creation of the aforementioned environment is possible due to specific training of the current academic staff and encouragement and professional training of future pedagogues. The experience revealed in the paper is based on the authors' work at the Faculty of Pedagogical Education of Borys Grinchenko Kyiv Metropolitan University, specifically with the students of specialties 012 Preschool Education and 013 Primary Education foreign language training.